Effects of Traditional Chinese Medicine on Gastrointestinal Dysfunction in Sepsis from Intestinal Flora - Li, Yang (International Journal of Public Health and Medical Research, 2025)
Gastrointestinal dysfunction in sepsis is a key link affecting the prognosis, and its occurrence is closely related to intestinal flora disorders. From the perspective of modern medicine, intestinal flora, this paper discusses the preventive and therapeutic effects of traditional Chinese medicine. The article first combed the understanding of gastrointestinal dysfunction of sepsis in traditional Chinese medicine, which belongs to the category of "intestinal obstruction" and "Guange", and the core of pathogenesis is "toxin damaging intestinal collaterals, fu-organ qi obstruction". The key role of intestinal flora imbalance, barrier function damage and immune inflammatory response out of control in morbidity was elaborated. This paper focuses on the synergistic mechanism of traditional Chinese medicine in multi-target regulation of flora structure, repair of intestinal barrier and inhibition of excessive inflammation through purgative, heat-clearing and detoxifying, spleen-invigorating and blood-activating therapy. The analysis shows that the intervention strategy of TCM based on the principle of "holistic concept" and "strengthening the body resistance and eliminating pathogens" is highly consistent with the inherent requirements of regulating "flora-intestine-axis", which provides a unique way of thinking for clinical prevention and treatment.